A review of peer-to-peer transaction loss and blockchain: challenges and drivers in the roadmap to a low-carbon future - P, Maya; Salam, P. Abdul (Frontiers in Energy Research, 2024)
Adapting to horizontal market structures faces several drivers and challenges in the context of sustainable energy transition. The inherently decentralized nature qualifies blockchain technology as the major technical driver in the transition to peer-to-peer (P2P) energy market models. One major technical challenge encountered in the transition process is the active power loss associated with transactions, which can cause network congestion and economic loss. A review of existing research on the P2P transaction active power loss problem, examining the potential role of blockchain and the consequent additional costs incurred by blockchain transactions, is presented in this article. Consolidating major points and guiding observations for future research are provided to address the challenges while adapting to the potential driving blockchain technology. A conceptual peer-to-peer trading framework that considers blockchain transaction cost and active power loss compensation is also presented.